2019
DOI: 10.1080/00207543.2019.1657249
|View full text |Cite
|
Sign up to set email alerts
|

Green product design with competition and fairness concerns in the circular economy era

Abstract: In this paper, we consider green product design in a supply chain consisting of one manufacturer and two retailers, where retailer 1 aims at monetary profit maximization, and retailer 2 has fairness concern. We consider two kinds of green products: a marginal-intensive green product (MIGP) and a development-intensive green product (DIGP). For the former, the green investment cost depends on the green level and the production quantity; while for the latter, the green investment cost depends on the green level s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 48 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…In the field of fairness concern, Yang et al [20] believed that the retailer's fairness concern brought disadvantages to him. Pu et al [21] found that the retailer's fairness concern could strongly influence the manufacturer's decisions and negatively affect the expected profits. Li et al [22] believed that the retailer's fairness concern hurt the manufacturer while putting himself at a disadvantage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of fairness concern, Yang et al [20] believed that the retailer's fairness concern brought disadvantages to him. Pu et al [21] found that the retailer's fairness concern could strongly influence the manufacturer's decisions and negatively affect the expected profits. Li et al [22] believed that the retailer's fairness concern hurt the manufacturer while putting himself at a disadvantage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A circular economy (Govindan and Hasanagic 2018;Howard, Hopkinson, and Miemczyk 2018) commonly refers to an economy or economic system which aims to be environmentally sustainable (Li et al 2019a(Li et al , 2019bCai and Choi 2019;Guo, Choi, and Shen 2020) with the minimisation of wastage and maximisation of activities such as reuse, recycle and remanufacturing (3R). The circular economy has been used in district planning (Liu et al 2012).…”
Section: Research In the Sharing And Circular Economy Eramentioning
confidence: 99%
“…They finally develop a simplified supply chain contract to enhance the performance of the retailer as well as social welfare. Li et al (2019a) investigate the circular supply chain using game theory with the paper entitled the 'Green Product Design with Competition and Fairness Concerns in the Circular Economy Era'. Similar to Shen, Xu, and Choi (2019), the authors also explore the 'optimal green product design' decision.…”
Section: Circular Economy and Environmental Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations